An in silico pipeline for subject-specific hemodynamics analysis in liver surgery planning. Issue 4 (11th March 2020) - Ho, H.; Yu, H. B.; Bartlett, A.; Hunter, P.
Abstract: The progresses in fast simulations of the hepatic flow in subject-specific vascular tree have created new toolkits for pre-surgical planning. The aim of this short communication is to introduce a computational pipeline that integrates several recently developed in silico liver models and algorithms. Firstly, a semi-automatic segmentation pipeline is used to digitise hepatic vessels. Then, a constructive constraint optimisation (CCO) algorithm is used to extend the digitised vascular tree, and also to compute the blood pressure and flow velocity in the tree. Couinaud segments are simulated from the diffusion zones of the portal venous tree. The constructed surgical planning model is then deployed cross-platform for use in various scenarios.